DESENVOLVIMENTO DE CURATIVO MULTIFUNCIONAL PARA TRATAMENTO DE FERIDAS CRÔNICAS POR TERAPIA FOTODINÂMICA - Grossko, Douglas (2021)
The chronic wounds healing it is a complex task and a public health issue. Therefore, the development of efficient bandages it is extremely important to the treatment of this kind of injury. Bandages that are made of electrospinning fibers have a three-dimensional porous structure that give the capability of absorbing exudates, diffusing vapours and allowing for cell proliferation by the material. The curcumin (CUR) incorporation as a photosensitizer to the photodynamic therapy (PDT) turns the electrospinning fibers a multifunctional material able to act in the healing process fighting infections and stimulating cell regeneration. Thus, the essence of this paper is in development of nanostructured materials through the electrospinning technique, incorporating the CUR to the PDT wound treatment. The physico-chemical study of photosensitizer has revealed that the CUR presents spectroscopic properties suitable to the treatment of superficial wounds. The fiber was electrospinning from polymer blends of polycaprolactone (PCL) and Pluronic® F-108. The scanning electron microscopy (SEM) showed the fiber formation of average diameters between 616 nm and 1134 nm. The release testing demonstrated a fast release rate that it is affected by the F-108 concentration. The results indicate a promising material to be used in the PDT wound treatment.